2013
DOI: 10.5923/j.pc.20120206.06
|View full text |Cite
|
Sign up to set email alerts
|

A First-Derivative Spectrophotometric Method for the Determination of Ciprofloxacin Hydrochloride in Ophthalmic Solution

Abstract: A sensitive, economical and reproducible derivative visible-spectrophotometric method for determination of ciprofloxacin hydrochloride in ophthalmic solution was developed and validated. The method is based on the development of yellow colored product due the reaction between ciprofloxacin hydrochloride and Fe (III). After the reaction, the spectra of the solutions were recorded in the range of 360-500 nm and the first-derivative spectra were obtained by instrumental electronic differentiation using a delta la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…[62][63][64][65] However, it is a non-selective method and is not suitable for the detection of degradation products and impurities. [66] Spectrophotometric methods are also found in literature for other fluoroquinolones, such as ciprofloxacin, [67] norfloxacin, [68,69] orbifloxacin, [70] lomefloxacin, [71] gatifloxacin, [72] and sparfloxacin. [73,74] Costa et al (2014) developed and validated a microbiological agar diffusion method for the potency analysis of besifloxacin in ophthalmic suspension.…”
Section: Uv (289 Nm)mentioning
confidence: 99%
“…[62][63][64][65] However, it is a non-selective method and is not suitable for the detection of degradation products and impurities. [66] Spectrophotometric methods are also found in literature for other fluoroquinolones, such as ciprofloxacin, [67] norfloxacin, [68,69] orbifloxacin, [70] lomefloxacin, [71] gatifloxacin, [72] and sparfloxacin. [73,74] Costa et al (2014) developed and validated a microbiological agar diffusion method for the potency analysis of besifloxacin in ophthalmic suspension.…”
Section: Uv (289 Nm)mentioning
confidence: 99%
“…Dexamethasone (8S,9R,10S,11S,13S,14S,1 6R,17R)-9-Fluoro-11,17-dihydroxy-17-(2-hydroxyacetyl)-10,13,16-trimethyl-, 7,8,9,10,11,12,13,14,15,16,17-dodecahydro-3H-cyclopenta[a] phenanthren-3-one [ Figure 1] a corticosteroid, is used to relieve bacterial ocular infections that require corticosteroid [1]. Many authors have reported a lot of different analytical methods for both drugs individually utilizing different techniques like HPLC [2][3][4][5][6][7][8][9], spectrophotometry and spectrofluorometric [10][11][12][13], titrimetric [14] methods for ciprofloxacin while for dexamethasone different methods involving HPLC, GC and TLC are reported [15][16][17][18][19][20][21].…”
Section: Ciprofloxacinmentioning
confidence: 99%
“…at λ of 275 nm in aqueous solution [19][20]22]. The similarity in physicochemical properties makes LEV-CPR ratio remained constant throughout the sample preparation.…”
Section: Introductionmentioning
confidence: 98%